Correlation and anti-correlation of the East Asian summer and winter monsoons during the last 21,000 years - Xinyu Wen (Nature Portfolio, 2016)
Future projection of changes in the East Asia Summer and Winter Monsoon are hindered by a lack of understanding of past variability. Here, using longterm transient simulations, the authors show that the monsoons respond in phase to precessional forcing, yet out of phase millennial-scale North Atlantic forcing.